Physiological and behavioural responses of Australian and exotic prey to the scent of native and introduced predators - Mella, Valentina S. A. (Curtin University, 2009)
This study examined the physiological and behavioural effects of a stress-inducing stimulus (predator odour) on potential prey species (Australian native and exotic). The aim was to determine if differences in the response of prey were related to the scent of evolutionary known predators compared to unfamiliar or short-term introduced ones. In laboratory experiments, responses were always restricted to changes in respiratory variables, with brushtail possums (Trichosurus vulpecula), rabbits (Oryctolagus cuniculus) and tammar wallabies (Macropus eugenii) showing no variation in metabolic rate after exposure to predator odours.Brushtail possums showed strong changes in ventilatory rate only when faced with the scent of an historical predator, increasing respiratory frequency (ratio after/before exposure = 4.55 ± 1.007) and decreasing tidal volume (ratio after/before exposure = 0.38 ± 0.113 ) in response to stale dingo urine. The changes were short-lived, lasting for only one minute of exposure. For this reason, it is unclear if the response observed could be considered as a fear reaction. However, there was no habituation after three exposures and this may indicate that possums were initially displaying an investigative approach to a predator scent and then relaxing once assessment was completed.The effect of predator and novel odours on the ventilation of rabbits appeared to be in general mediated by anxiety, as shown by the responses elicited by both predator and control scents. However, stronger reactions were observed in response to feral cat and quoll odours for both respiratory frequency (ratio after/before exposure to feral cat = 4.39 ± 0.721 and to quoll = 3.75 ± 0.486) and tidal volume (ratio after/before exposure to feral cat = 0.47 ± 0.065 and to quoll = 0.64 ± 0.129). This could be due to different intensity of the olfactory stimuli. Nevertheless, the effects of noxious odours on rabbits clearly demonstrate that they become highly vigilant at any sudden change in their environment.Tammar wallabies appeared to possess a mechanism for the recognition of predator odours as ventilatory responses were restricted to particular predator scents. After investigation, fox and cat odour provoked a stronger and more prolonged change in respiratory frequency (ratio after/before exposure to fox = 3.58 ± 0.918 and to feral cat = 2.44 ± 0.272) and tidal volume (ratio after/before exposure to fox = 0.84 ± 0.110 and to feral cat = 0.98 ± 0.155) compared to the other scents, suggesting that wallabies may have perceived these species as more immediate threats.For wild, free-living brushtail possums and southern brown bandicoots (Isodoon obesulus), there was no pattern of avoidance of historical or introduced predator odours, with no difference in number of animals captured in predator and control scented traps. This may indicate that predator odour avoidance has not evolved in these species and that they have poor possibilities of escaping potential predators. However it may also be explained by the long-term predator-free environment in which the study was conducted, and suggests loss of anti-predator behaviour in populations without predation risk.Wild, free-ranging western grey kangaroos (Macropus fuliginosus) reacted to the odour of both historical (dingo) and novel (fox) predators by reducing number of feeding events (5.2±2.08 for fox and 5.9±1.33 for dingo) and time spent foraging (17.7±7.2 sec for fox and 22.2±4.6 sec for dingo) when predator scents were present and by escaping areas tainted with predator odours (41.4±17.5 sec for fox and 33.8±13 sec for dingo). Clearly these results suggest that kangaroos are scared of predator odours. However, a close investigation of predator scents was necessary before a response could be elicited and feeding areas were not completely abandoned.It is still unclear if small Australian prey, such as southern brown bandicoots and brushtail possums, respond to olfactory cue of predation in the wild, as different results were obtained in the studies conducted in the laboratory and in free populations. However, this research showed that medium and large-sized macropods respond to both native, long-term and introduced predator odours. This indicates that at least some Australian prey species can recognise the odour of potential predators, although responses usually occur after a period of investigation, and do not always result in avoidance behaviour. Differential responses appear to be based on the perceived risk. Use of predator odour is unlikely to be an effective mechanism of deterring herbivores from preferred feeding locations.